Aspergillus meningitis in a patient with chronic lymphocytic leukemia. Issue 6 (June 2020) - Matsuo, Takahiro; Mori, Nobuyoshi; Sakurai, Aki; Furukawa, Keiichi
Abstract: Central nervous system aspergillosis is relatively rare and difficult to diagnose. Here, we report a case of 90-year-old man with chronic lymphocytic leukemia who presented with a month-long gradually worsening headache followed by 3 days of low-grade fever associated with altered mental status. Aspergillus meningitis diagnosed using Aspergillus galactomannan antigen in the cerebrospinal fluid and treated with voriconazole. Delayed diagnosis and treatment of Aspergillus meningitis is typically associated with high mortality; therefore, it is imperative to include this disease in the differential diagnoses of subacute meningitis.